PENGGUNAAN MODEL PEMBELAJARAN QUANTUM TEACHING TERHADAP HASIL BELAJAR SENI RUPA PADA MATA PELAJARAN SENI BUDAYA SISWA KELAS X SMAN 1 JUNJUNG SIRIH KABUPATEN SOLOK - NUCI GUSTIA, Dr.Ramalis Hakim, M.Pd. Drs. Ariusmedi, M.Sn (Serupa The Journal of Art Education, 2014)
This research firstly conducted by observing the teacher of art which isconcentrate on teaching fine arts in SMAN 1 Junjung Sirih where the teachercould not make a good classroom interaction because she did not serve the learning materials with varieties of ways . The result from the preliminary observation were: 1) the teacher had not created the good learning environment for the students, 2) had not achieved the goal of the learning objectives completely, 3) had not built a background knowledge of the students, 4) had not given a reinforcement for the students completely, 5) had not celebreted the students improvement. Quantum teaching is one of the solution to make the good classroom interaction as long the learning process and can help the students to improve their academic qualification.This research is a Quantitative research which used experimental design.The population of this research was the students at the tenth grade of SMAN 1 Junjung Sirih, meanwhile the sample that was choosen through random sampling were X IPA and X IPA . the total number of the students for each class was 26 students. after that, the researcher did lottery in order to decide the experimental class and the control class. the lottery revealed that the experimental class was for X IPA and the control class was X IPA. Learning outcomes are seen in this study is the cognitive domain. The data analysis technique used to test the hypothesis was t-test where the sample is normally distributed and have homogeneous variance.T-test result of the study is 3,12 while t-table is 1,675 (T − test > T −table ) where H is refused and H  accepted or proven . From this result, it can be concluded that Quantum Teaching Model can help the students to improve their academic qualification especially in finearts subject and it is a better model of teaching than the conventional model of teaching.